PENGATURAN PENGHENTIAN PEMAKAIAN INDIKASI GEOGRAFIS PADA MEREK TERDAFTAR OLEH PIHAK LAIN YANG TIDAK BERHAK (STUDI KOMPARATIF BEBERAPA NEGARA) - I GEDE AGUS KURNIAWAN (Jurnal Magister Hukum Udayana (Udayana Master Law Journal), 2013)
TRIPs requires members to arrange to any intellectual property rights in accordance with the conditions of each country, so that each state set the Geographical Indication (GI) varies. The different settings are potential conflicts between TRIPs member countries. So the research problem of this thesis is: How IG arrangements relating to cessation of the use of the registered mark is associated with a state's territory IG TRIPs Agreement? and legal actions for users How IG to a dispute between members of the TRIPs? Research using normative legal research methods approach: Statue Approach, Conceptual Approach, Comparative Approach, and Analytical Approach. Analysis of legal materials is done by descriptive analysis. The results showed that each WTO member countries set different. For example, the United States set up through the Trademark Law, Regulation & Legal ATF habits, countries under the European Union set up the European Community Regulation (EEC No.2081/92), Vietnam: Intellectual Property Law (Law No.50-2005-QH11), and others. In general, countries that determine protection through a first to file system. The use of registered GIs in the same marks or identical, Singapore set specifically in the Geographical Indications Act 44 of 1998, the Indonesian Though not set in isolation, but more specifically set in Trademark Law Article 56 (8) PP. 51 of 2007, Article 27 (1) and (2) termination of the use of signs to be discontinued within 2 years after the IG registered. The results also showed a lot of disputes going on in the field of IG Efforts settlement can be reached through WTO mechanisms if the parties to a dispute between the State by State with DSU procedures, WIPO mechanism is used if the dispute between the individual and the individual (state) with WAC procedures. National mechanisms such as in Indonesia through a lawsuit at the Commercial Court (Pengadilan Niaga).